Enhanced drug delivery and wound healing potential of berberine-loaded chitosan–alginate nanocomposite gel: characterization and in vivo assessment - Akhter, Md Habban; Al-Keridis, Lamya Ahmad; Saeed, Mohd; Khalilullah, Habibullah; Rab, Safia Obaidur; Aljadaan, Adel M.; Rahman, Mohammad Akhlaquer; Jaremko, Mariusz; Emwas, Abdul-Hamid; Ahmad, Sarfaraz; Alam, Nawazish; Ali, Md Sajid; et al. (Frontiers in Public Health, 2023)
Berberine-encapsulated polyelectrolyte nanocomposite (BR-PolyET-NC) gel was developed for long acting improved wound healing therapy. BR-PolyET-NC was developed using an ionic gelation/complexation method and thereafter loaded into carbopol gel. Formulation was optimized using design-expert software implementing 3-level 3-factor Box Behnken design.The concentration of polymer (chitosan/alginate), calcium chloride was investigated on particle size, and %EE. Moreover, formulation characterized in vitro for biopharmaceutical performances and their wound healing potency was evaluated in vivo in adult Balb C mice. The particle distribution analysis showed nanocomposite size of 71 ± 3.5 nm, PDI of 0.45, ζpotential of +22 mV, BR entrapment of 91 ± 1.6%, and loading efficiency of 12.5 ± 0.91%.Percentage drug release was recorded 89.50 ± 6.9% in pH 6.8 simulating micro-wound environment. The in vitro investigation of nanocomposite gel revealed uniform consistency, well spreadability, and extrudability which are ideal for topical wound use. The analytical estimation executed using FT-IR, DSC, and X-ray diffraction indicated successful formulation with no drug-excipients and amorphous state. The colony count of microbes was greatly reduced in the treatment group of BR-PolyET-NC upto 6 cfu on 15 th day vis-à-vis to 20 cfu for BR-gel. The numbers of monocytes, lymphocytes counts were significantly reduced following healing progression reached to a peak level and vanish on 15 th days. The observed experimental characterization and in vivo study suggested effectiveness of developed BR-PolyET-NC gel towards wound closure and healing process i.e., >99% of wound was closed on 15 th day, stimulated via various anti-inflammatory and angiogenic factors.